FGFR2 residence in primary cilia is necessary for epithelial cell signaling - Nita, Alexandru; Abraham, Sara P; Elrefaay, Eman R; Fafilek, Bohumil; Cizkova, Eliska; Ursachi, Vlad Constantin; Gudernova, Iva; Koudelka, Adolf; Dudeja, Pooja; Gregor, Tomas; Feketova, Zuzana; Rico, Gustavo; et al. (The Journal of cell biology, 2025)
Primary cilium projects from cells to provide a communication platform with neighboring cells and the surrounding environment. This is ensured by the selective entry of membrane receptors and signaling molecules, producing fine-tuned and effective responses to the extracellular cues. In this study, we focused on one family of signaling molecules, the fibroblast growth factor receptors (FGFRs), their residence within cilia, and its role in FGFR signaling. We show that FGFR1 and FGFR2, but not FGFR3 and FGFR4, localize to primary cilia of the developing mouse tissues and in vitro cells. For FGFR2, we demonstrate that the ciliary residence is necessary for its signaling and expression of target morphogenic genes. We also show that the pathogenic FGFR2 variants have minimal cilium presence, which can be rescued for the p.P253R variant associated with the Apert syndrome by using the RLY-4008 kinase inhibitor. Finally, we determine the molecular regulators of FGFR2 trafficking to cilia, including IFT144, BBS1, and the conserved T429V430 motif within FGFR2.
Keywords: myši; receptor fibroblastových růstových faktorů, typ 2; epitelové buňky; signální transdukce; Signal Transduction; Cilia; Epithelial Cells; receptor fibroblastových růstových faktorů, typ 1; zvířata; Mice; Humans; Receptor, Fibroblast Growth Factor, Type 1; Receptor, Fibroblast Growth Factor, Type 2; lidé; cilie; Animals